The impact of natural disasters on energy consumption: An analysis of renewable and nonrenewable energy demand in the residential and industrial sectors - Doytch, Nadia (Archīum Ateneo, 2017)
This study examines the impact of infrastructure‐damaging natural disasters (meteorological and geophysical disasters) on energy consumption differentiating by type of energy: residential versus industrial and nonrenewable versus renewable. We used a novel comprehensive unbalanced data set spanning 50 years (1961–2011) for up to 80 countries, which we group by level of development to reduce heterogeneity within the group. We applied an estimation method that takes into account the dynamics of the economic processes in the panel: the Blundell and Bond GMM estimator. For high‐income economies, which are also technologically the most advanced, we are able to demonstrate a positive impact on renewable energy use 5 years after the occurrence of a geophysical disaster. For low‐income economies, we observe positive effects on industrial energy consumption; for middle‐income countries, on residential energy consumption.